Acute lung injury after aortic surgery: the relation between lung and leg microvascular permeability to 111indium-labelled transferrin and circulating mediators. Issue 10 (October 1997) - Raijmakers, P G; Groeneveld, A B; Rauwerda, J A; Teule, G J; Hack, C E
Abstract : BACKGROUND: Aortic surgery is a risk factor for acute lung injury and this may relate to ischaemia/reperfusion (I/R) of the lower body and release of inflammatory mediators. The aim of this study was to define the changes in microvascular protein permeability and circulating inflammatory mediators after aortic surgery. METHODS: In 11 consecutive patients who underwent elective aortic surgery microvascular permeability in lung and leg was measured before and a median of 2.8 hours after completion of surgery using 111indium (In)-labelled transferrin and 99mtechnetium (Tc)-labelled red blood cells, yielding a protein leak index (PLI) that is specific for protein permeability. Circulating leucocyte counts and levels of inflammatory mediators were determined. RESULTS: In the lung the PLI rose from a median of 0.6 (range -0.5 to 2.2) x 10(-3)/min before surgery to 5.4 (-2.3 to 33.5) x 10(-3)/min after surgery, and in the leg from 0.3 (-1.6 to 1.7) x 10(-3)/min to 5.0 (1.0 to 27.8) x 10(-3)/min. The increase in PLI in the lung was related to that in the leg. Levels of activated complement C3a and tumour necrosis factor-alpha did not change, but levels of interleukin (IL)-6, IL-8 and elastase-alpha 1-antitrypsin increased. After surgery there was slight neutrophilia and the leucocyte counts were inversely related to the IL-8 level. The rise in lung but not in leg PLI was greatest in patients with the highest IL-8 levels and the lowest leucocyte counts. CONCLUSIONS: Early after aortic surgery microvascular protein permeability increases in the leg and lung. Leg I/R injury may result in neutrophil activation and release of IL-8, which may induce neutrophil sequestration and subsequently increased pulmonary microvascular permeability. These findings may help to explain the occurrence of acute lung injury after I/R in man.